Desenvolvimento de biomateriais para liberação de fármacos a base de titânio e colágeno - Ferreira, Carlise Hannel (2019)
In the present study, TiO2 coatings grown in an electrolytic medium based on ethylene glycol and PBS were investigated as drug delivery devices. The nanotubes were grown from pure Ticp titanium and Ti6Al4V alloy. In order to delay the release of the drug (ciprofloxacin), collagen was used as a diffusional barrier. After a synthesis and the coating was characterized in relation to the morphology, microstructure and contact angle for the coatings. In the morphological characterization, it was observed an internal diameter of NTs around 10nm smaller for the alloy in relation to NTs grown without pure titanium. In the microstructural characterization, we noticed a larger increase in crystal size for the thin films grown in Ticp. Moreover, no study of angle of observation for both substrates the anodization time also influenced a wettability, reducing humidity with increasing anodization time. The release kinetics analysis indicates the release of CIPRO since then with the mechanism of release of the onset of Fick's kinetics and then the interaction of the drug with the surface of the oxide can delay the release time. Biomaterials adhere to the binding to the longer cycle of the drug cycle compared to pure titanium, this is due to the higher surface area of the bond. In biological assays the inhibition halo is for any sample the inhibition of the microorganism is efficient at least 12 times the size of the implant. And for hemocyte hemocyte in vaccines. Toxic to blood cells and the release of the drug released during the holding test below the toxic concentration, a bacteriostatic activity.